Cultivating compassion through compassion circles: learning from experience in mental health care in the NHS. Issue 1 (18th October 2021) - Clark, Michael; Bradley, Andy; Simms, Laura; Waites, Benna; Scott, Alister; Jones, Charlie; Dodd, Paul; Howell, Tom; Tinsley, Giles
Abstract : Purpose: This paper aims to discuss the importance of compassion in health care and experiences of Compassion Circles (CCs) in supporting it, placing this into the national policy context of the National Health Service (NHS), whilst focusing on lessons from using the practice in mental health care. Design/methodology/approach: This conceptual paper is a discussion of the context of compassion in health care and a description of model and related concepts of CCs. This paper also discusses lessons from implementation of CCs in mental health care. Findings: CCs were developed from an initial broad concern with the place of compassion and well-being in communities and organisations, particularly in health and social care after a number of scandals about failures of care. Through experience CCs have been refined into a flexible model of supporting staff in mental health care settings. Experience to date suggests they are a valuable method of increasing compassion for self and others, improving relationships between team members and raising issues of organisational support to enable compassionate practice. Research limitations/implications: This paper is a discussion of CCs and their conceptual underpinnings and of insights and lessons from their adoption to date, and more robust evaluation is required. Practical implications: As an emergent area of practice CCs have been seen to present a powerful and practical approach to supporting individual members of staff and teams. Organisations and individuals might wish to join the community of practice that exists around CCs to consider the potential of this intervention in their workplaces and add to the growing body of learning about it. It is worth further investigation to examine the impact of CCs on current concerns with maintaining staff well-being and engagement, and, hence, on stress, absence and the sustainability of work environments over time. Social implications: CCs present a promising means of developing a culture and practice of more compassion in mental health care and other care contexts. Originality/value: CCs have become supported in national NHS guidance and more support to adopt, evaluate and learn from this model is warranted. This paper is a contribution to developing a better understanding of the CCs model, implementation lessons and early insights into impact.